SIRT4 Is Highly Expressed in Retinal Müller Glial Cells - Wei, Wei; Hu, Piaopiao; Qin, Mengqi; Chen, Guiping; Wang, Feifei; Yao, Shengrui; Jin, Ming; Xie, Zhi; Zhang, Xu (Frontiers in Neuroscience, 2022)
Sirtuin 4 (SIRT4) is one of seven mammalian sirtuins that possesses ADP-ribosyltransferase, lipoamidase and deacylase activities and plays indispensable role in metabolic regulation. However, the role of SIRT4 in the retina is not clearly understood. The purpose of this study was to explore the location and function of SIRT4 in the retina. Therefore, immunofluorescence was used to analyze the localization of SIRT4 in rat, mouse and human retinas. Western blotting was used to assess SIRT4 and glutamine synthetase (GS) protein expression at different developmental stages in C57BL/6 mice retinas. We further analyzed the retinal structure, electrophysiological function and the expression of GS protein in SIRT4-deficient mice. Excitotoxicity was caused by intravitreal injection of glutamate (50 nmol) in mice with long-term intraperitoneal injection of resveratrol (20 mg/Kg), and then retinas were subjected to Western blotting and paraffin section staining to analyze the effect of SIRT4 on excitotoxicity. We show that SIRT4 co-locates with Müller glial cell markers (GS and vimentin). The protein expression pattern of SIRT4 was similar to that of GS, and both increased with development. There were no significant retinal structure or electrophysiological function changes in 2-month SIRT4-deficient mice, while the expression of GS protein was decreased. Moreover, long-term administration of resveratrol can upregulate the expression of SIRT4 and GS while reducing the retinal injury caused by excessive glutamate. These results suggest that SIRT4 is highly expressed in retinal Müller glial cells and is relevant to the expression of GS. SIRT4 does not appear to be essential in retinal development, but resveratrol, as an activator of SIRT4, can upregulate GS protein expression and protect the retina from excitotoxicity.